The physical characteristics of match-play in English schoolboy and academy rugby union. Issue 6 (19th March 2018) - Read, Dale B.; Jones, Ben; Phibbs, Padraic J.; Roe, Gregory A. B.; Darrall-Jones, Joshua; Weakley, Jonathon J. S.; Till, Kevin
ABSTRACT: The aim was to compare the physical characteristics of under-18 academy and schoolboy rugby union competition by position (forwards and backs). Using a microsensor unit, match characteristics were recorded in 66 players. Locomotor characteristics were assessed by maximum sprint speed (MSS) and total, walking, jogging, striding and sprinting distances. The slow component (<2 m · s −1 ) of PlayerLoad TM (PLslow ), which is the accumulated accelerations from the three axes of movement, was analysed as a measure of low-speed activity (e.g., rucking). A linear mixed-model was assessed with magnitude-based inferences. Academy forwards and backs almost certainly and very likely covered greater total distance than school forwards and backs. Academy players from both positions were also very likely to cover greater jogging distances. Academy backs were very likely to accumulate greater PLslow and the academy forwards a likely greater sprinting distance than school players in their respective positions. The MSS, total, walking and sprinting distances were greater in backs ( likely - almost certainly ), while forwards accumulated greater PLslow ( almost certainly ) and jogging distance ( very likely ). The results suggest that academy-standard rugby better prepares players to progress to senior competition compared to schoolboy rugby.